Engaging and mobilizing youth for Agriculture Development - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Ntiokam Divine, YPARD Country Representative, Cameroon shares his views on youth engagement and mobilization for Agricultural development. The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/ http://www.fara-africa.org/scienceweek/